To develop and optimize a Self-Nanoemulsifying Drug Delivery System (SNEDDS) for enhancing the oral bioavailability of poorly water-soluble itraconazole drugs. - Ketan Albhar; Amit Kasabe; Vaibhav Wagh (International Journal of Medical Toxicology and Legal Medicine, 2024)
The main objective of this study was to enhance the bioavailability of Itraconazole, a BCS II antifungal drug with poor water solubility, by developing a self-Nanoemulsifying drug delivery system (SNEDDS). Poor water solubility and bioavailability are significant challenges for many drugs. This study aims to enhance the solubility and bioavailability of ITZ through the development of a Self-Nanoemulsifying Drug Delivery System (SNEDDS). Preformulation studies including Fourier Transform Infrared Spectroscopy (FTIR), Differential Scanning Calorimetry (DSC), and X-ray Diffraction (XRD) confirmed the purity, crystalline nature, and absence of drug-excipient interactions. Pseudo-ternary phase diagrams were constructed to identify optimal ratios of oil, surfactant, and co-surfactant, selecting Capmul MCM, Tween 20, and Lutrol E 400 as key components. Fifteen trial formulations (IF1 to IF15) were prepared and evaluated for drug content, self-emulsification time, and in vitro drug release. Among them, formulation IF6 demonstrated the highest drug content (95.26%), rapid self-emulsification (50 seconds), and superior cumulative drug release, indicating efficient solubilization and potential for improved bioavailability. Statistical analysis using ANOVA confirmed the significant impact of Capmul MCM on drug content and self-emulsification time. The DSC and XRD results indicated successful amorphization of ITZ in the optimized formulation. Overall, the SNEDDS approach significantly enhanced the solubility, dissolution rate, and potential bioavailability of ITZ, presenting a promising strategy for improving the therapeutic efficacy of poorly water-soluble drugs.